2020
DOI: 10.1016/j.idairyj.2020.104762
|View full text |Cite
|
Sign up to set email alerts
|

Review of the prevalence of foodborne pathogens in milk and dairy products in Ethiopia

Abstract: Food safety is a significant barrier to social and economic development throughout the world, particularly in developing countries. Here, we reviewed the prevalence of major bacterial foodborne pathogens ( Salmonella spp., Listeria monocytogenes , Escherichia coli O157:H7 and Campylobacter spp.) in the rapidly growing Ethiopian dairy supply-chain. We identified 15, 9, 5 and 0 studies that had reported the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 70 publications
1
52
0
2
Order By: Relevance
“…Numerous epidemiological reports have implicated nonheat treated milk and raw-milk products as the major factors responsible for illnesses [ 9 11 ], Hence, zoonotic risk arising from this milk should be considered [ 12 ]. However, in Afar region in general and in Dubti district in particular, there is scarcity of information on camel mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous epidemiological reports have implicated nonheat treated milk and raw-milk products as the major factors responsible for illnesses [ 9 11 ], Hence, zoonotic risk arising from this milk should be considered [ 12 ]. However, in Afar region in general and in Dubti district in particular, there is scarcity of information on camel mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…Control measures in the manufacture of dairy products are essential to prevent contamination by microorganisms from animal or environmental sources (POPPE, 2020). KEBA et al (2020) indicated the prevalence of Salmonella spp. and L. monocytogenes in dairy foods and raw milk and explained that the adoption of hygiene practices at all stages of the chain is essential to avoid the incidence of these pathogens in dairy products.…”
Section: Resultsmentioning
confidence: 99%
“…Milk is the most consumed dairy product in the globe ( FAO, 2013 ). Although milk and milk products are lucrative sources of nutraceuticals such as proteins, calcium, and vitamin D, they might be contaminated to some pathogenic microorganisms, including Listeria monocytogenes , Salmonella spp., Campylobacter jejuni , and E. coli O157: H7 ( Keba et al, 2020 ). Thus, heat treatment of milk is mandatory in most countries during industrial processing, as it ensures the safety of milk consumption.…”
Section: Various Transmission Routes Of Sars-cov-2 and The Probable Fmentioning
confidence: 99%